Implikasi Erupsi Gunung Agung Terhadap Sosial Ekonomi Pelaku Usaha Pariwisata Di Kawasan Pantai Batu Bolong, Canggu - Sasmita, Dewi; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 7 No 2 (2019): VOL 7, NO 2 (2019): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i02.p14, 2019)
The eruption of Mount Agung has an immense impact on Bali, especially in the economic sector of the tourism business. The locations which are far from Gunung Agung have been affected especially in the Southern part of Bali which has a higher growth of tourism compared to the rest. This is interesting to study especially in the tourism related business namely the Batu Bolong Beach area. The purpose of this study is to determine the post- eruption implications of Mount Agung that have hit Bali in terms of the socio-economic aspects of tourism stakeholders and the existing business conditions in the Batu Bolong Beach area. As well as knowing the crisis management system in the tourism in Batu related business at Batu Bolong Beach and seeking at the situation and condition those who work for tourism related businesses at the Batu Bolong Beach area.The research methodology used in this study is qualitative research. Where qualitative uses in-depth interview techniques, observations and qualitative documents as well as using the concept of socio-economic impacts of tourism to see the socio-economic impacts arising from the eruption of Mount Agung. The results shows the conditions of tourism businesses after the eruption, theses include: type of business, product range and price, tourist visits, post-eruption economic income. Another result is the socioeconomic condition of tourism stakeholder in the Batu Bolong Beach area. Key word: Implication social economic tourism, Mount Agung Eruption, Tourism business